Semi-Analytical Method for Solving Coupled Nonlinear Partial Differential Equations Using Hybrid Iterative Method - S. Hasan, Nisreen; Al-Fayadh, Ali (Al-Nahrain Journal of Science, 2024)
This article aims to propose a new efficient hybrid method for solving different types of nonlinear differential equations. The method combines mixed Shehu and Sumudu integral transforms with the variational iteration method. The proposed method is termed the multiple transform iteration method to solve different nonlinear partial differential equations, by engaging a new time and frequency domain. The outcomes that arise from this method show the efficiency, accuracy, and simplicity of applying the approach.